Equal Policies, Rules, and Witnesses Implemented to Address the Challenges of Sexual Harassment in the Workplace - Sugeng Santoso PN; Alivia Hasnanda Sakina Maheswari; Andari Yurikosari; Joshua Avandeo Irawan (Private Law, 2026)
This study examines the persistent issue of workplace sexual harassment across nations, despite existing laws and regulations. Utilizing a qualitative, normative juridical approach, it compares the policies and penalties in Indonesia, Malaysia, China, and the USA. Findings reveal that while all four countries enforce laws against sexual harassment, their approaches differ significantly. Indonesia primarily punishes offenders, lacking protections for victims, unlike Malaysia and the USA, which offer compensation and safeguard rights. The study underscores the necessity for global regulations that impose strict penalties on offenders and employers, ensure proper investigations, and protect victims' rights, promoting a unified stance against workplace harassment.